The Influence of Perceptions of Organizational Support, Work Stress, Organizational Commitment, and Job Satisfaction on Employee Performance In The Automotive Industry - Kustiawan, Unggul; Septiyaningsih, Septiyaningsih; Syah, Tantri Yanuar Rahmat; Rojuaniah, Rojuaniah; Budiman, Arief (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The objective of this research is to explore the effect of perceived organizational support, work stress, organizational commitment, and job satisfaction on employee performance, which then builds organizational commitment and job satisfaction so as to give rise to employee performance, which has a good impact on productivity and enterprise. Data collection was carried out by distributing questionnaires online using a Google Form, which resulted in 205 respondents working for automotive industry companies in the Cikarang and Karawang industrial areas. Data analysis and processing using Lisrel 8.8 software The findings of this study indicate that perceived organizational support has a negative effect on work stress and a positive effect on organizational commitment. When employees feel there is no organizational support, this triggers stress. Work stress has no negative effect on job satisfaction, and organizational commitment has a positive effect on job satisfaction. Meanwhile, job satisfaction has a positive effect on employee performance. The results of this study are expected to provide valuable insights for the company. With a better understanding of these factors, companies can increase employee productivity and achieve company goals.